2020
DOI: 10.1038/s41598-020-65331-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-128-3p Enhances the Chemosensitivity of Temozolomide in Glioblastoma by Targeting c-Met and EMT

Abstract: Temozolomide is a first line anti-tumor drug used for the treatment of patients with Glioblastoma multiforme (GBM). However, the drug resistance to temozolomide limits its clinical application. Therefore, novel strategies to overcome chemoresistance are desperately needed for improved treatment of human GBM. Recent studies have demonstrated that miRNAs are closely related to resistance to cancer chemotherapy. This study aimed to further validate the biological role of miR-128-3p and to investigate whether miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Notch1 plays an instrumental part in glioma cells, with the functions of enhancing stemness and tumorigenicity 33,34 , promoting tumor growth 35 , EMT 36 , and increasing chemotherapy drug resistance 37 . In this study, we used shRNA to inhibit the expression levels of Notch1 in glioma cells, and we revealed that EMT (N-cadherin and Vimentin decreased, E-cadherin increased), proliferation, migration, and invasion ability of cancer cells were signi cantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Notch1 plays an instrumental part in glioma cells, with the functions of enhancing stemness and tumorigenicity 33,34 , promoting tumor growth 35 , EMT 36 , and increasing chemotherapy drug resistance 37 . In this study, we used shRNA to inhibit the expression levels of Notch1 in glioma cells, and we revealed that EMT (N-cadherin and Vimentin decreased, E-cadherin increased), proliferation, migration, and invasion ability of cancer cells were signi cantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…c-MET was recently shown to mediate EMT via activation of Wnt/b-catenin signaling (65). MiR-128-3p targeting c-MET inhibited glioblastoma migration and invasion and enhanced TMZ therapeutic efficacy in vivo (66). Other miRNAs such as miR-34a, miR-144-3p, and miR-562 have been reported to exert activity against glioblastoma proliferation and invasion by also targeting c-MET (66)(67)(68).…”
Section: C-metmentioning
confidence: 99%
“…MiR-128-3p targeting c-MET inhibited glioblastoma migration and invasion and enhanced TMZ therapeutic efficacy in vivo (66). Other miRNAs such as miR-34a, miR-144-3p, and miR-562 have been reported to exert activity against glioblastoma proliferation and invasion by also targeting c-MET (66)(67)(68). Hence, these therapeutic miRNAs and c-MET siRNAs could be used to treat glioblastoma by means of suppressing tumor invasion and EMT.…”
Section: C-metmentioning
confidence: 99%
“…In fact, the average survival time for glioblastoma patients is only 14 months [ 4 ]. Due to the heterogeneity of gliomas [ 5 ] and different drug resistance to temozolomide (TMZ) [ 6 9 ], the prognosis of different glioma patients is quite different. Meanwhile, the application of high-throughput technology for the molecular classification of gliomas as well as for screening differentially expressed genes and drug resistance genes has become a research hotspot to facilitate the development of corresponding targeted drugs.…”
Section: Introductionmentioning
confidence: 99%